Longitudinal dimensionality affects repetitive strength in skiers - Durlevic, S.; Mijajlovic, M.; Durlevic, M.; Ilic, I. (Journal of Anthropology of Sport and Physical Education, 2024)
Skiing belongs to a group of activities that take place in special conditions of the external environment, and success in skiing primarily depends on morphological characteristics, motor and functional abilities. Accordingly, the aim of the research is to identify the structure of longitudinal dimensionality and repetitive power of skiers, and then examine the potential influence of longitudinal dimensionality on repetitive power of skiers. The sample of respondents consisted of 21 skiers with chronological age 16.04±2.51. The sample of measuring instruments consisted of nine variables, five variables for the assessment of morphological characteristics: body height (BH), leg length (LL), upper leg length (LUL), lower leg length (LLL) and arm length (LA), and four variables for repetitive strength testing: push-ups until failure (PUF), sit ups until failure (SUF), chin ups until failure (CUF) and squats until failure (SQUF). The influence of longitudinal dimensionality on the repetitive strength of skiers was determined using linear regression analysis. All statistical analyzes were performed with the statistical package IBM SPSS Statistics (Version 20). The results showed that the area of longitudinal dimensionality is dominantly defined by body height (BH), while the area of repetitive strength is defined by the squat until failure test (SQUF). Using linear regression, it is confirmed that there is a statistically significant influence of longitudinal dimensionality on the repetitive strength of skiers.